2012
DOI: 10.1016/j.fob.2012.11.005
|View full text |Cite
|
Sign up to set email alerts
|

A cataract‐causing connexin 50 mutant is mislocalized to the ER due to loss of the fourth transmembrane domain and cytoplasmic domain

Abstract: Mutations in the eye lens gap junction protein connexin 50 cause cataract. Earlier we identified a frameshift mutant of connexin 50 (c.670insA; p.Thr203AsnfsX47) in a family with autosomal recessive cataract. The mutant protein is smaller and contains 46 aberrant amino acids at the C-terminus after amino acid 202. Here, we have analysed this frameshift mutant and observed that it localized to the endoplasmic reticulum (ER) but not in the plasma membrane. Moreover, overexpression of the mutant resulted in disin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Studies of certain connexin mutants linked to congenital cataracts have implicated hemichannels with aberrant voltage-dependent gating or modulation by divalent cations in disease pathogenesis [25]. Further deletion analysis has shown that the fourth transmembrane domain (M4) and a membrane proximal region (codons 231-294) of the cytoplasmic domain are needed for transport from the endoplasmic reticulum and localization to the plasma membrane [30]. However, unlike previously characterized Cx50 mutants that exhibited impaired intracellular transport and subsequent insertion into the plasma membrane and/or lack of function, the Cx50 mutant p.G46V with functional hemichannels and gap junction channels causes cell death even when expressed at minute levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of certain connexin mutants linked to congenital cataracts have implicated hemichannels with aberrant voltage-dependent gating or modulation by divalent cations in disease pathogenesis [25]. Further deletion analysis has shown that the fourth transmembrane domain (M4) and a membrane proximal region (codons 231-294) of the cytoplasmic domain are needed for transport from the endoplasmic reticulum and localization to the plasma membrane [30]. However, unlike previously characterized Cx50 mutants that exhibited impaired intracellular transport and subsequent insertion into the plasma membrane and/or lack of function, the Cx50 mutant p.G46V with functional hemichannels and gap junction channels causes cell death even when expressed at minute levels.…”
Section: Discussionmentioning
confidence: 99%
“…Since there are many different derangements in the cellular/ biochemical behavior and function of the Cx50 mutants, further functional impact of the mutant protein on cell growth [16,42] or hemichannels voltage-dependent gating [30,43], will improve our understanding of the underlying pathogenesis of cataract formation and illuminate the role of the connexin family in the lens. Also, since this is a dominant disease, it would be really interesting to assess whether the mutant protein dimerize with the wild-type form would impede the proper localization or function of the wild-type [44], which would help to design possible genetic therapies in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The second was an autosomal recessive c.607dup p.(Thr203Asnfs*47) change reported in two affected children in an Indian family, with heterozygous parents and relatives all presenting as unaffected [129]. This variant resulted in the loss of the second extracellular domain through to the C-terminal protein tail, with both this variant and a truncated p.Thr203Ter protein shown to result in disrupted localization to the plasma membrane and retention in the endoplasmic reticulum [130].…”
Section: Autosomal Recessive Variants In Gja8mentioning
confidence: 99%